2018
DOI: 10.1016/j.vetmic.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit haemorrhagic disease: Cross-protection and comparative pathogenicity of GI.2/RHDV2/b and GI.1b/RHDV lagoviruses in a challenge trial

Abstract: European rabbits (Oryctolagus cuniculus) are severely affected by rabbit haemorrhagic disease (RHD). Caused by a lagovirus, the disease leads to losses in the rabbit industry and has implications for wildlife conservation. Past RHD outbreaks have been caused by GI.1/RHDV genotype viruses. A new virus belonging to the GI.2/RHDV2/b genotype emerged in 2010, quickly spreading and replacing the former in several countries; however, limited data are available on its pathogenicity and epidemiological factors. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
76
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(90 citation statements)
references
References 33 publications
(29 reference statements)
11
76
3
Order By: Relevance
“…All of the 37 wild rabbits were also qPCR-positive for the same virus at mean (SD) Cq values of 18.7 (2.04). This value is in agreement with Calvete et al (2018), who reported Cq values ranging from 18.03 to 18.30 using the same qPCR procedures in rabbits that had died from acute RHD caused by the same virus. Although qPCR was not developed to quantify viral RNA copy numbers (Calvete et al 2018), the high Cq values found in the small mammals suggested a lower quantity of viral particles than in rabbits killed by acute disease.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…All of the 37 wild rabbits were also qPCR-positive for the same virus at mean (SD) Cq values of 18.7 (2.04). This value is in agreement with Calvete et al (2018), who reported Cq values ranging from 18.03 to 18.30 using the same qPCR procedures in rabbits that had died from acute RHD caused by the same virus. Although qPCR was not developed to quantify viral RNA copy numbers (Calvete et al 2018), the high Cq values found in the small mammals suggested a lower quantity of viral particles than in rabbits killed by acute disease.…”
supporting
confidence: 92%
“…The results of the qPCR analysis were negative for all tissue samples except for the liver and the spleen of the surviving rabbit challenged with the Cr-Jun15-P4 inoculum. In this instance, GI.2/RHDV2/b RNA was found with high Cq values in the spleen and liver (40.5 and 42, respectively), which were, nevertheless, out of the lowest limit of detection (Cq¼38.7) established for qPCR (Calvete et al 2018). Seroconversion was detected in two surviving rabbits: one challenged with Cr-Feb15-P1 inoculum, and the survivor from the Cr-Jun15-P4 inoculum challenge.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…A large 362 proportion of rabbits present in every shot sample were >500 days old, and may therefore confound 363 the analysis of recent virus activity. In addition, if some level of immunological cross protection 364 exists between RHDV and RHDV2 (Calvete et al, 2018), the removal of susceptible rabbits by an 365 RHDV2 outbreak from the population could result in an apparent increase of RHDV seroprevalence, 366 due to the resulting increased proportion of surviving old RHDV seropositive animals in the sample. 367…”
Section: Discussion: 310mentioning
confidence: 99%